N-Chlorosuccinimide: A Versatile Reagent in Organic Synthesis - Nimbhal, Aman; Singh, Ram (Current Organic Chemistry, 2025)
N-Chlorosuccinimide (NCS) is a five-membered N-containing heterocyclic molecule. This is a versatile reagent and is successfully employed for different types of reactions. Initially, this was employed for chlorination only but soon became an excellent reagent for many reactions, including halocyclizations, functional group transformations, formation of carbon-carbon bonds, etc. This review article covers representative applications of NCS for aliphatic and aromatic chlorination, chlorination of atoms other than carbon, oxidation, and other reactions.
Keywords: N-chlorosuccinimide